On the Determinant of Interest rate Derivative by UK non financial companies - UBAH, EMMANUEL (2017)
This study empirically investigates the determinants of interest rate hedging and the determinants of the extents of interest rate hedging by UK nonfinancial firms. The sample consist of 400 firms over the period of one year 2015-2016, where a key word approach was employed to collect data on firms’ interest rate hedging activities. Univariate and Multivariate tests indicates that interest rate hedging is prominent in larger firms. The use of continuous measure for interest rate hedging strengthens the results of these factors being relevant determinants of the level of interest rate hedging.